Land cover of Łódź Voivodeship in the years 2000–2018 in the light of Corine Land Cover data - Nalej, Marta (Acta Geographica Lodziensia, 2019)
The aim of the author was to analyse land cover and its changes in the Łódź Voivodeship in the years 2000–2018. Based on CORINE Land Cover data and using GIS tools, analysis of land cover and its changes were performed for three intervals – the years 2000–2006, 2006–2012 and 2012–2018 – in spatial and quantitative terms. This approach allowed the land cover of the studied area to be characterised and the directions, intensity and spatial distribution of changes to be captured. In the study the density of changes was measured using the method of density distribution estimation with the use of non-para-metric nuclear estimators – the kernel function.